Contribution of Plasmodium knowlesi to multi-species human malaria infections in North Sumatera, Indonesia - Inke, ND Lubis; Hendri, Wijaya; Munar, Lubis; Chairuddin P, Lubis; Paul Cliff, Simon Divis; Khalid, B Beshir; Sutherland, Colin J (Oxford University Press, 2017)
Background As Indonesia works towards the goal of malaria elimination, information is lacking on malaria epidemiology from some western provinces. As a basis for studies of antimalarial efficacy, we set out to survey parasite carriage in three communities in North Sumatera Province.